2020
DOI: 10.1037/neu0000623
|View full text |Cite
|
Sign up to set email alerts
|

Diminished social attention in pediatric brain tumor survivors: Using eye tracking technology during naturalistic social perception.

Abstract: Objective:The etiology of pediatric brain tumor survivor (PBTSs) social difficulties is not well understood. A model of social competence for youth with brain disorder and evidence from youth with autism spectrum disorder (ASD) suggests that diminished social attention may underlie social deficits in PBTSs. This study used eye tracking technology to compare visual social attention in PBTSs, youth with ASD, and typically developing (TD) youth. Methods: Participants included 90 age-, gender-, and IQ-matched yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Additional neuroimaging research, particularly longitudinal studies and those that have sufficient samples to evaluate the effects of specific treatment variables (e.g., radiation field and dose), is needed to determine the neurobiological processes underlying the social difficulties of PBTS. Findings from the current study provide an important perspective for prior research with PBTS showing reduced facial affect recognition accuracy (Bonner et al, 2008;Moxon-Emre et al, 2019) and diminished gaze preference for faces when observing social interactions (Hocking et al, 2020). Hypoactivation in the specialized face processing areas of the fusiform gyrus may underlie these social information processing difficulties in survivors and contribute to a negative feedback loop.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Additional neuroimaging research, particularly longitudinal studies and those that have sufficient samples to evaluate the effects of specific treatment variables (e.g., radiation field and dose), is needed to determine the neurobiological processes underlying the social difficulties of PBTS. Findings from the current study provide an important perspective for prior research with PBTS showing reduced facial affect recognition accuracy (Bonner et al, 2008;Moxon-Emre et al, 2019) and diminished gaze preference for faces when observing social interactions (Hocking et al, 2020). Hypoactivation in the specialized face processing areas of the fusiform gyrus may underlie these social information processing difficulties in survivors and contribute to a negative feedback loop.…”
Section: Discussionmentioning
confidence: 57%
“…Another study, showed face processing to be uniquely important to the social functioning of PBTS (Hocking et al, 2021). Further, recent evidence suggests that PBTS gaze less at faces during social situations than TD youth and in a manner consistent with youth with ASD (Hocking et al, 2020) suggesting reduced experience in processing facial information. Two recent studies have evaluated the neurobiological factors associated with the face processing abilities of PBTS (Moxon-Emre et al, 2019;Moxon-Emre et al, 2020), focusing on associations between the processing of facial expressions and structural connectivity (e.g., white matter).…”
mentioning
confidence: 94%
“…Regarding measurement, the present study incorporated only parent report measures for the assessment of social outcomes. Although parent ratings provide meaningful information and are commonly used in clinical settings, other studies have noted the benefits of sociometric approaches, computer‐based measures of social information processing, and interviews for the evaluation of survivor social outcomes 3,4,53,54 . The lack of self‐report measures is another limitation and may lead to under‐ or overestimation of social challenges depending on caregiver awareness of social difficulties experienced by survivors outside of the home.…”
Section: Discussionmentioning
confidence: 99%
“…Although parent ratings provide meaningful information and are commonly used in clinical settings, other studies have noted the benefits of sociometric approaches, computer-based measures of social information processing, and interviews for the evaluation of survivor social outcomes. 3,4,53,54 The lack of self-report measures is another limitation and may lead to under-or overestimation of social challenges depending on caregiver awareness of social difficulties experienced by survivors outside of the home. Future studies will benefit from carefully selected methods for measuring survivor selfreported social functioning, including an interview format permitting clarification.…”
Section: Limitationsmentioning
confidence: 99%
“…While the 5‐year survival rates for children with brain tumors has increased dramatically, 1,2 late effects are common and include weaknesses in neurocognition, 3,4 social functioning, 5–7 and delayed psychosocial development 8 . Deficits in social functioning in survivors of pediatric brain tumors (PBTS) have been most frequently assessed via parent, teacher, or self‐report questionnaires, or peer nominations as a means of assessing social acceptance 9–11 .…”
Section: Introductionmentioning
confidence: 99%